Motivation of management students to engage in volunteering (in the light of research results) = Motywacja studentów kierunków menedżerskich do angażowania się w wolontariat (w świetle wyników badań) - Stankiewicz, Janina; Seiler, Bartosz; Bortnowska, Hanna (Zielona Góra: Faculty of Economics and Management Press)
Market of volunteers in Poland, especially those ones with specialized skills, is limited. An important reservoir of volunteer work are the universities. Non-governmental organizations should consider sustained cooperation with them. Volunteers predisposed to provide administrative support could be sought among the students of management.
Keywords: organizacje non profit; wolontariusze; motywacja; studenci kierunków menedżerskich; non profit organizations; volunteers; motivation; management students